The ECB's Monetary Analysis Revisited - Berger, Helge (IMF Working Papers; Working Paper, 2008)
Monetary aggregates continue to play an important role in the ECB's policy strategy. This paper revisits the case for money, surveying the ongoing theoretical and empirical debate. The key conclusion is that an exclusive focus on non-monetary factors alone may leave the ECB with an incomplete picture of the economy. However, treating monetary factors as a separate matter is a second-best solution. Instead, a general-equilibrium inspired analytical framework that merges the economic and monetary "pillars" of the ECB's policy strategy appears the most promising way forward. The role played by monetary aggregates in such unified framework may be rather limited. However, an integrated framework would facilitate the presentation of policy decisions by providing a clearer narrative of the relative role of money in the interaction with other economic and financial sector variables, including asset prices, and their impact on consumer prices.